TEKANAN EKONOMI, STRATEGI KOPING, DAN KETAHANAN KELUARGA YANG MENIKAH USIA MUDA - Herawati, Tin; Tyas, Fatma Putri Sekaring; Trijayanti, Lely (Jurnal Ilmu Keluarga dan Konsumen, 2017)
Early marriage family refer to united people by blood or adoption, consisting of husband, wife, children and other family members in which one of husband or wife or both of them are married under 20 years old. The purpose of this study was to analyze the correlation and the influence of economic pressure and coping strategy on family strength among early marriage family. The study was conducted in the Cihideung Udik village and Tegal Waru village, Ciampea Sub District, Bogor Distr. The samples of this research were families who the husband or wife or both were under 20 years old when they were married and had children who aged 0-6 years old. There were 70 mothers of sample families as respondents. This research showed that the family economic pressures were in the the medium category, family coping strategies were in the low category, and family strength were in the medium category. Family strength affected by length of marriage, number of family member, and economic pressure. Moreover, the number of family members and length of marriage had a significant positive influence on family strength. On the other hand, economic pressures had a significant negative influence on family strength. Further research is expected to involve husband in interviews and to involve some variables that can give a comprehensive empirical evidence to explore the life of early marriage family; such as family resource management, family adjustment, intimacy of married couples, and child development of young couples.